A Clinical and Economic Comparison of Cell-Based Versus Recombinant Influenza Vaccines in Adults 18–64 Years in the United States - Myron J. Levin; Neda Al Rawashdh; Liliane Mofor; Pablo Anaya; Richard M. Zur; Emily B. Kahn; Daniel Yu; Joaquin F. Mould-Quevedo (Vaccines)
Background: This analysis compares the cost-effectiveness of a cell-based influenza vaccine to a recombinant influenza vaccine, and each to no vaccination. The analysis is based on United States (US) commercial and societal perspectives. Methods: A Susceptible–Exposed–Infectious–Recovered (SEIR) transmission model of the total US population followed with a cost-effectiveness model for 18–64-year-olds was used to estimate the clinical and economic impact of vaccination over one influenza season (2018–2019). Deterministic and probabilistic sensitivity analyses were conducted. Results: Both enhanced vaccines prevented a substantial number of influenza cases and influenza-related deaths compared to no vaccination. The cell-based vaccine was associated with higher quality-adjusted life years (QALYs) gained compared to the recombinant vaccine or no vaccination. The cell-based vaccine had a 36% lower vaccination cost, amounting to $2.8 billion in cost savings, compared to the recombinant vaccine. The incremental cost-effectiveness ratios (ICERs) for the cell-based vaccine, compared to the recombinant vaccine or no vaccination, were dominant from all payer perspectives, regardless of risk groups. Conclusions: Overall, the cell-based vaccine was cost-saving compared to the recombinant vaccine for subjects aged 18–64 years in the US, achieving comparable health outcomes with a significant reduction in associated costs.